PENGARUH UPSKILLING DAN MOTIVASI KERJA TERHADAP PENINGKATAN KINERJA MANAJEMEN BILLING (Suatu Studi Pada PT PLN (Persero) Unit Layanan Pelanggan Ciamis Bagian Transaksi Energi Listrik) - Dudi Hermawan; Faizal Haris Eko Prabowo; Enjang Nursolih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the suboptimal performance of employees at PT. PLN (Persero) ULP Ciamis which is caused by suboptimal upskilling and work motivation. The formulation of the problem in this study is: How do upskilling (job training) and work motivation influence billing management performance at PT. PLN (Persero) ULP Ciamis, both partially and simultaneously?? The method used in this study is a survey method with a quantitative approach. The population in this study is the billing management employees of PT. PLN (Persero) ULP Ciamis, namely 102 employees, the selected sample is 81 people. In this study, data collection was carried out through several techniques, namely literature studies, field studies and questionnaire distribution. The research results suggest the following conclusions: Upskilling has a positive and significant impact on the performance of billing management employees at PT PLN (Persero) ULP Ciamis, Electrical Energy Transaction Division. Work motivation has a positive and significant impact on the performance of billing management employees at PT PLN (Persero) ULP Ciamis, Electrical Energy Transaction Division. Upskilling and work motivation have a positive and significant impact on the performance of billing management employees at PT PLN (Persero) ULP Ciamis, Electrical Energy Transaction Division.